Manajemen Peningkatan Mutu Berbasis Sekolah - Hidayat, Lihsan; Marwiji, Muh. Hasan (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
The success of implementing the MPMBS really depends on the ability of the school principal to be able to play an active role in school management by empowering all components involved in school administration, especially in empowering the community as a whole. However, the implementation cannot be separated from supporting and inhibiting factors. For this reason, this study examines, deepens the concepts and matters relating to the implementation of the MPMBS program, especially in educational institutions. This research is library research, which is research based on searching the literature related to the issues to be discussed. The data in this library research is obtained through digging and tracing books, articles, magazines, journals, internet access and other important related notes. The results of this study reveal the supporting factors for the implementation of MPMBS in an educational institution, namely: having strong leadership, having a clear vision and mission as well as goals and objectives, a safe, orderly and conducive school environment, the participation of parents / guardians of students in supporting their children's education. and the role of the school committee in providing support to schools. While the inhibiting factors include: incomplete facilities and infrastructure, minimal funding, low discipline culture and enforcement of madrasah rules, the concept and objectives of the MPMBS are not well understood, school residents and interested parties and the role of the community in helping school programs have not maximum.